Developing global citizenship - Kuzma, Lynn M. (Groupwork, 2012)
This article explores an attempt to develop global citizenship through a service-learning experience that placed undergraduate students in community organizations that serve refugee populations. It begins with a discussion of the importance of civic engagement in higher education and how service learning, as a pedagogical method, can advance the goals of civic engagement and community building. It discusses how groupwork in class, with service providers, and with refugees led to increased civic awareness and transformed student dispositions toward diverse community groups.